Network simulation with NS3 - Ha, Duc Vinh (2010)
In this project, the network simulation tool NS3 will be studied. NS3 is free and open source network simulation software. The performance analysis of some selected network environment will be performed using this NS3 software. Churning behavior of mobile users and TCP congestion control are simulated using Ns-3 in this project works. Churning behavior of mobile users from one service provider to another is expected to become common features when the users have freedom to choose the best service among several services. This churning characteristics impacts both technical and economical aspect of network design and usage. The decisions of users in the migration process in choosing the best service are base on the performance as well as price offered. In this project, the model of churning behaviors of wireless users is studied using simulation method based on the theory of evolutionary game. The system model built consisting of WLAN hotspots where users may choose to associate with base one performance parameters and price. The connection departure and arrival were captured as well as rational and irrational churning behaviors of service users. The simulation is done using Network Simulator III (NS-3) and expected have feature similar to the actual deployment. The strategies of users in selecting the services provider are based on trade off between through put versus price of the service they use. The result focus on the evolutionary equilibrium points which present the average number of users choosing a certain service provider. Analysis of outcomes is performed and compare with the theory model and used for proposed modeling framework.